Upregulation of miR-133b and miR-328 in Patients With Atrial Dilatation: Implications for Stretch-Induced Atrial Fibrillation - Masè, Michela; Grasso, Margherita; Avogaro, Laura; Nicolussi Giacomaz, Manuel; D’Amato, Elvira; Tessarolo, Francesco; Graffigna, Angelo; Denti, Michela Alessandra; Ravelli, Flavia (Frontiers in Physiology, 2019)
Atrial stretch and dilatation are common features of many clinical conditions predisposing to atrial fibrillation (AF). MicroRNAs (miRs) are emerging as potential molecular determinants of AF, but their relationship with atrial dilatation is poorly understood. The present study was designed to assess the specific miR expression profiles associated with atrial dilatation in human atrial tissue. The expressions of a preselected panel of miRs, previously described as playing a role in cardiac disease, were quantified by reverse transcription-quantitative polymerase chain reaction in atrial tissue samples from 30 cardiac surgery patients, who were characterized by different grades of atrial dilatation and arrhythmic profiles. Our results showed that atrial dilatation per se was associated with significant up-regulation of miR-328-3p and miR-133b (p<0.05) with respect to controls, with a fold-change of 1.53 and 1.74, respectively. In a multivariate model including atrial dilatation and AF as independent variables, miR-328-3p expression was mainly associated with atrial dilatation grade (p<0.05), while miR133b was related to both atrial dilatation (p<0.005) and AF (p<0.05), the two factors exerting opposite modulation effects. The presence of AF was associated with significant (p<0.05) up-regulation of the expression level of miR-1-3p, miR-21-5p, miR-29a-3p, miR-208b-3p, and miR-590-5p. These results showed the existence of specific alterations of miR expression associated with atrial dilatation, which may pave the way to future experimental studies to test the involvement of post-transcriptional mechanisms in the stretch-induced formation of a pro-arrhythmic substrate.